2010
DOI: 10.1007/s00586-010-1404-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of one-level minimally invasive and open transforaminal lumbar interbody fusion in degenerative and isthmic spondylolisthesis grades 1 and 2

Abstract: Minimally invasive lumbar fusion techniques have only recently been developed. The goals of these procedures are to reduce approach-related soft tissue injury, postoperative pain and disability while allowing the surgery to be conducted in an effective manner. There have been no prospective clinical reports published on the comparison of one-level transforaminal lumbar interbody fusion in low-grade spondylolisthesis performed with an independent blade retractor system or a traditional open approach. A prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
207
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(224 citation statements)
references
References 18 publications
14
207
2
1
Order By: Relevance
“…Some surgeons have suggested that MI-TLIF could increase surgical time [6,7]. Secondly, to facilitate a minimally invasive approach, more X-ray exposure was used [4,[7][8][9]. Thirdly, MI-TLIF has a steep learning curve and is a technically demanding procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some surgeons have suggested that MI-TLIF could increase surgical time [6,7]. Secondly, to facilitate a minimally invasive approach, more X-ray exposure was used [4,[7][8][9]. Thirdly, MI-TLIF has a steep learning curve and is a technically demanding procedure.…”
Section: Introductionmentioning
confidence: 99%
“…However, only limited Class I evidence is available [4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The objective of the present study was to provide cumulative effect estimates of the clinical and radiological outcomes using meta-analysis and to determine which surgical technique was more beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…An MIS approach to the lumbar spine decreases iatrogenic soft tissue injury and theoretically improves dynamic muscular stabilization at an index level [17,[37][38][39][40][41]. MIS techniques also pose several potential advantages for use in obese patients in terms of decreased incision length, blood loss, operative time, hospital stay and post-operative pain where abundant subcutaneous adipose tissue may necessitate a larger incision and dissection for adequate exposure when utilizing a traditional open approach.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the favorable outcomes of MIS-TLIF accompanied by spinal instrumentation with percutaneous pedicle screw insertion and decompression in degenerative spondylolisthesis [1,3,5,12,20,21,23,25]. In the presence of severe spinal canal stenosis and distorted facet anatomy due to severe FJO, MIS techniques however could limit direct visualization of neural elements and pedicle screws relative to key anatomical structures and could increase the rate of complications and pedicle screw misplacement.…”
Section: Introductionmentioning
confidence: 99%